Mass-Transfer Characteristics of Air- Suction Type Fermentors - M., Alaa K. (Al-Khwarizmi Engineering Journal, 2019)
Liquid-side mass-transfer coefficients (KLa) were measured in air-suction type fermentors using physical absorption of oxygen.  A fermentor of 0. 5 m i.d. was used with a working capacity of 60 liters of liquid. Tap water was used as the liquid phase, and air was used as the gas phase. The bioreactor mixing system consists of shrouded-disk/curved-blade turbine with six evacuated bending blades. The effect of liquid submergence (S) was investigated. Further, the effects of the ratio of the impeller diameter (D) to the tank diameter (T), and the clearance of the impeller from the tank bottom(C) were also studied.  The agitation speed (N) was varied in the range of 50-800 rpm. It was found that the value of  KLa increased as the impeller diameter  increased, while it was decreased continuously with increasing the clearance. the effect of impeller submergence on the value of mass transfer coefficient (KLa) is not much pronounced.Suitable correlation was developed for estimating mass transfer coefficient (KLa) in this type of bioreactors.